A Digital-Based Training on Making Processed Fish Crackers for MSMEs Sinar Mutiara - Fatimah, Siti; Yanastiar, Atep; Azizah, Aulia Nur; Budiyanto, Rizki (Jurnal Pengabdian Masyarakat Bestari, 2024)
Sinar Mutiara MSME located in Karang Serang Village, Tangerang Regency, Banten Province, produces quality fish crackers with interesting innovations. Made from fresh fish ingredients and hygienic manufacturing processes, these fish crackers make a healthy and delicious everyday snack. The practical packaging makes these crackers suitable for traveling or enjoying at home. Free of preservatives and artificial colors, Tish Fish Crackers are safe for consumption by all groups and have gained wide recognition among our loyal customers. This research method uses a qualitative method that begins with lectures, discussions, exercises, and evaluations. The service activities not only provide theoretical and practical knowledge to students, but also training in making mackerel fish crackers. Through this training, MSMEs are expected to get interesting recipes for processed fish crackers.